Evapotranspiration for irrigated agriculture using orbital satellites - Althoff, Daniel (2019)
Acknowledging the importance of evapotranspiration as a mediating factor for efficient irrigation management and water balance, the objective of study is to compare the Simple Algorithm for Evapotranspiration Retrieving (SAFER) to the standard method proposed by FAO-56 for real evapotranspiration, as well as prove its value as an implement in irrigation management for the Brazilian Savanna. Data used refers to 2015’s harvest of seven center pivots, located in the municipality of São Desidério in western Bahia. For the SAFER algorithm, the images used were acquired by the Landsat-8 satellite during the entire maize crop cycle. The SAFER algorithm estimation demonstrates the spatial and temporal distribution of the evapotranspiration. A maximum evapotranspiration of 5.38 mm d-1 was observed during the crop’s reproductive stage. In relation to the standard method, SAFER showed a mean absolute error of 0.40 mm. Thus, concluding that the algorithm can be used to estimate the actual evapotranspiration crop as an alternative to the standard method proposed by FAO-56 for water resources management.